Evaluacion del sistema name por maiz intercalado con yuca, caupi y ajonjoli en la Costa Atlantica - Arrieta B., J.M. (International Center for Tropical Agriculture, 1990)
The results of several expt. carried out at the Centro Regional de Investigacion El Carmen, with different arrangements of the cropping system yam x maize intercropped with cassava or other crops, are presented. Maize var. ICA V 155, yam var. Peludo, and cassava var. Venezolana were used, planted at 1 x 1 m. Yam was planted manually and maize hill-plot planted (4 grains/site). Of all the arrangements tested, yam associated with maize intercropped with cassava gave the highest net returns (Col $271,200), with a LER coefficient of 2.0, indicating that 2 times the relative land area of monocropped cassava or maize or yam are needed to obtain the same total production of the system. (CIAT)